Digital literacy: How mobile augmented reality titration in acid-base titrations facilitated the skill - Sari, Maya; Muntholib, Muntholib; Habiddin, Habiddin; Sumari, Sumari (Eclética Química, 2026)
Augmented reality media is used in chemistry education to enhance digital literacy skills, which are essential for higher education in the twenty-first century, and to provide titration simulations that reduce the need for chemicals. By producing media based on augmented reality and facilitating the understanding of acid-base titration, this initiative aims to enhance students’ digital literacy. A product called Mobile Augmented Reality Titration (MART) was created by implementing the Ploomp approach. Content validation demonstrates the high legitimacy and validity of the produced media. A post-test group design research study with 60 participants, split between control and experimental classes, was used to gauge the effectiveness of digital literacy abilities. The empirical test findings found a substantial difference in digital literacy skills between the experimental and control groups, as indicated by Cohen’s D value of 3.85. This suggests that the rise of augmented reality media has substantially impacted the ability to learn acid-base titrations through digital literacy.